Mínimo (2017)
"Mínimo, a ceramics studio that I built with the main objective of developing my own design impersonation. Mínimo, founded from the analysis and transformation of the minimalist movement created in the early sixties is based upon a minimalist interpretation. The brand generates a new perspective based on my early footprints as a designer, the use of geometry, research for new orders and constant investigation regarding materials and shapes." -- Tomado del Formato de Documento de Grado.